Exploring relationships between geological structures delineated from high resolution geophysical data collected over 1:50,000 mapsheets 2229AB Mapungubwe and 2229AD Coila, Beit Bridge Terrane, Central Zone, Limpopo Belt, South Africa - Havenga, Marinda (My University, 2014)
High resolution aeromagnetic and radiometric data covering the 1:50,000 mapsheets 2229AB Mapungubwe and 2229AD Coila were collected by the Council for Geoscience and interpreted in this study. Several generations of magnetised lineaments were identified and modelled as mafic dykes. North-northwest, east-northeast and east-west trending lineaments occur in the pre-Karoo basement (~2.04 Ga to Dwyka) and east-west trending lineaments predominate in Karoo sediments (<183 Ma). A number of circular magnetic anomalies occur in north-northwest and east-northeast trending clusters in the southwest of the study area. These were interpreted to be intrusive plugs – possibly feeders for the dolerite sills and dykes that occur in the area. Radiometric data delineate geological units within the pre-Karoo basement. Granitic to granodioritic rocks (2.6 Ga) are enriched in uranium and thorium while tonalitic rocks are not. Geological cross-sections, constructed along flight lines and tie-lines, suggest that there are two or more sills at depth under the southwestern portion of the study area intruded by the Venetia kimberlite pipes. In addition a large strongly magnetic anomaly with no surface expression was identified in the northeastern area and modelled to be at about 1200 m depth.
Thesis (M.Sc.)--University of the Witwatersrand, Faculty of Health Sciences, 2013.
Keywords: Geological mapping.; Environmental mapping.; Mapungubwe Site (South Africa)